A broker framework for selecting secure cloud service provider using security risk approach. (2016) - Talbi, Jamal; Haqiq, Abdelkrim
Cloud computing is a rising field providing computation resources. It represents a new paradigm of utility computing and enormously growing phenomenon in the present IT industry and economy hype. The companies which provide services to customers are called as cloud service providers. The cloud users (CUs) increase and require secure, reliable and trustworthy cloud service providers (CSPs) from the market. So, it is a challenge for a new customer to choose the highly secure provider. In this paper, we propose a broker framework that analyse and rank the cloud service providers based on measuring the risks of confidentiality, integrity and availability. This model uses a CSP rank framework for the group of cloud providers by assessing security metrics which make decision of the more secure provider among the available providers list and justify the business needs of users in terms of security and reliability.